Pengaruh Model Reflektif dan Minat Belajar terhadap Hasil Belajar Iman Katolik pada Siswa SMP dan SMA di Kota Bengkulu - Sinaga, Juliana (Vocat : Jurnal Pendidikan Katolik, 2025)
The low student attendance in Catholic Religious Education class indicates a challenge in fostering learning interest and the effectiveness of teaching methods. This study aims to analyze the influence of the reflective model and learning interest towards the outcomes of Catholic faith education among junior and senior high school students in Bengkulu city. The research employed a quantitative approach with a correlational design. The sample consists of 102 students selected purposively from a total of 144 students. Data was collected using a Likert scale questionnaire and analyzed through multiple regression using SPSS software. The results show that the reflective model does not have a significant effect on learning outcomes, while learning interest tends to have a positive influence, though not statistically significant. Simultaneously, these two variables do not significantly impact the outcomes of Catholic faith education. These findings confirm that the results of Catholic faith education are not solely determined by pedagogical factors but also by the depth of spiritual reflection and the motivation to teach in a more reflective, participatory manner that fosters a living faith experience aligned with the spirit of Evangelii Gaudium no. 11